The natural pest control potential of different landscapes - Peitz, Charlotte (2021)
Natural pest control describes the process of natural enemies suppressing pests and thus reducing crop damage and stabilizing yields. How well these beneficial arthropod predators and parasitoids can thrive in a landscape is influenced by the land-use types in the vicinity, such as forest patches, pastures, or agricultural fields, and their ability to provide resources. While the relationship between these landscape structures and specific insects is relatively well explored, up-scaling these findings from field experiments to larger areas is difficult. This thesis aims to contribute to a better understanding of this issue by mapping the natural pest control potential of three agricultural landscapes in Sweden, based on the presence of specific landscape factors. In order to do so, an expert survey was conducted with the aim to generate quantitative scores linking the influential land-use types to the abundance of natural enemies, which is used as an indicator for the natural pest control potential. Factors investigated were: Herbaceous and forested semi-natural habitat, as well as agricultural fields defined by variations of management types, field size and crop rotation diversity. The entirety of natural enemies was divided into three groups to account for a more precise response: complete generalists, more specialized predators, and parasitoids. These scores were then included in a spatially explicit model, based on which comprehensive maps depicting the natural pest control potential in parts of Dalarna, Västra Götaland and Scania were created. The experts rated herbaceous habitat and forest edges highly in their ability to support natural enemies. The scores of agricultural fields were equally high or partially higher if managed organically, having a small field size and a diverse crop rotation, while ratings were lower for conventional, large scale fields with a simplified rotation. The maps reveal that Scania and Västra Götaland have large amounts of high natural pest control potential, the largely forested Dalarna has lower values. While modelling this process required many simplifications and the reliability of the data is only ‘moderate’, the results can still give valuable insights into the complex issue. Especially promising are the high scores attributed to the diversification and extensification of agricultural fields, allowing to increase natural pest control without having to convert production areas to semi-natural habitats. Concrete farming practices identified include among others the reduced application of pesticides, the cultivation of fields at a smaller width and longer crop rotations, as well as a reduction of tillage and the cultivation of flower strips. The implementation of these practices on a landscape level requires policy makers to incentivize them properly and support farmers in making these changes. Furthermore, stakeholders need to create land management plans to increase the structural diversity in landscapes through e.g., the amount of semi-natural habitats. The thus increased natural pest control in our agricultural landscapes can contribute greatly to reducing the reliance on insecticides and the environmental damages connected to them, and plays a vital part in the transition to an ecological intensification.